Evaluation Of Antitumor Activity Of Copper Complexes Of Coumarin In Breast And Lung Cancer - Dalal M. Ibrahim,; Juliana Jumal; Farah Wahida Harun (IDOSI Publications, 2024)
Considerable interest has been aroused for copper complexes of coumarins due to their wide variety of biological activity. Three copper complexes of coumarin; A1, A2 and A3 were synthesized and evaluated for antitumor activity by using MTT assay. These complexes show antitumor activity against breast cancer MCF7 with IC values of 1.87, 1.87 and 30?g/ml respectively and exhibit 50 antitumor activity against lung cancer A549 with IC50 values of 7.5, 15 and 1.87?g/ml respectively.